2019
DOI: 10.1186/s40634-019-0212-6
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality-based navigation system applied to tibial bone resection in total knee arthroplasty

Abstract: BackgroundThis pilot study was performed to examine the accuracy of the AR-KNEE system, an imageless navigation system using augmented reality (AR) technology for total knee arthroplasty. The AR-KNEE system enables the surgeon to view information from the navigation superimposed on the surgical field on a smartphone screen in real time.MethodsUsing the AR-KNEE system, one surgeon resected 10 tibial sawbones with viewing the tibial axis and aiming varus/valgus, posterior slope, internal/external rotation angles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 25 publications
(29 reference statements)
3
48
0
Order By: Relevance
“…However, they did not evaluate any femur or tibia resection. The latter reported by Tsukada et al [ 11 ] reported a pilot study using sawbones where authors suggested that the AR may provide reliable accuracy for coronal, sagittal, and rotational alignment in tibial bone resection during total knee arthroplasty.…”
Section: Resultsmentioning
confidence: 99%
“…However, they did not evaluate any femur or tibia resection. The latter reported by Tsukada et al [ 11 ] reported a pilot study using sawbones where authors suggested that the AR may provide reliable accuracy for coronal, sagittal, and rotational alignment in tibial bone resection during total knee arthroplasty.…”
Section: Resultsmentioning
confidence: 99%
“…We performed CT of the resected Sawbones and measured the varus/valgus angle in the coronal plane and flexion/extension angle in the sagittal plane using computer software (ZedKnee; LEXI) 9 . To measure these angles, we established a 3-D coordinate system according to the following definition: (1) the x axis refers to the line connecting the sulcus of the medial epicondyle and the most prominent point of the lateral epicondyle, (2) the y axis refers to a line perpendicular to the plane formed by the center of the femoral head and the midpoint of the mediolateral width of the resected distal part of the femur, and (3) the z axis refers to a line perpendicular to both the x and y axes.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the AR-KNEE system does not require any preoperative imaging studies. Although the AR-KNEE system was shown to be accurate to within <1° in both coronal and sagittal planes in resection of the proximal part of the tibia 9 , there have been no studies to date assessing the accuracy of this system in distal femoral resection.…”
mentioning
confidence: 99%
“…In arthroplasty, exact implantation of the prosthetic components with respect to the patient’s anatomy is a main contributor to successful outcomes, functional recovery, and longevity [ 32 , 34 , 36 ]. Three studies performed on sawbones evaluated AR navigation of arthroplasties as more accurate than free-hand procedures in hip [ 32 , 36 ] and knee surgery [ 33 ].…”
Section: Clinical Applications Of Armentioning
confidence: 99%
“…The AR method was faster 1.8 ± 0.25 vs 3.9 ± 1.6 minute; p < .01. sawbone Tsukada et al 2019[ 33 ] Arthroplasty (knee) Navigation for tibial bone resection markers attached to bone and instruments Monitor The results presented comparable accuracy of this AR system for bone resection compared to conventional navigation systems (not specified). The study tested a proof of concept and is not recommended for clinical use at this state of the system by the authors.…”
Section: Introductionmentioning
confidence: 97%